«ЕР ҚОСАЙ» ДӘСТАНЫНДА ТЕҢЕЎЛЕРДИҢ ҚОЛЛАНЫЛЫЎЫ - Бекбаулиев, Қ.О. (SCIENCE and SOCIETY, 2025)
The article explores the function and features of using comparisons as a means of artistic depiction in the plot of the Karakalpak heroic epic "Yer Kosay." In the plot of the dastan, the role of comparisons in revealing the ideological content and creating images is described with examples.